Role of clusters in the Polish innovation system - Marta Mackiewicz (Central European Economic Journal (CEEJ), 2019)
This article presents the role of clusters in the Polish innovation system. This role has evolved in recent years due to maturing of cluster organisations and the expansion of their ability not just to provide services for cluster members but also to perform selected public tasks. This study aims to provide a better understanding of the nature and extent to which clusters can contribute to the objectives of development policies and thus to the economic development of the Polish economy and answer the question what role clusters can play in the innovation system. Based on a survey of 44 cluster organisations in Poland and interviews with cluster managers, the study explores the possibility of engaging Polish cluster organisations in the implementation of public policies. The results confirm that many of the Polish clusters achieved such a level of development that they themselves see the possibility of engaging in public tasks, for example education and specialised training, helping enterprises in digital transformation, monitoring technological trends, and so on. Therefore, it is justified pursuing a dual cluster policy. This duality means focus on two objectives: supporting cluster organisations on the one hand and implementing cluster-based development policies on the other hand.
Keywords: O25; O32; O38; 330; clusters; cluster initiatives; cluster organisations; cluster policy; innovation system